Natural Bioactive Cyclopeptides from Microbes as Promising Anticancer Drug Leads: A Mini-review - Sukmarini, Linda (Indonesian Journal of Pharmacy, 2021)
Natural products from microbes are a rich source of bioactive molecules to serve as drug leads, predominantly in cancer therapy. Peptides are among the essential nature-derived biomolecules. Owing to their great diversity and favorable characteristics, cyclic peptides (cyclopeptides) from natural sources have become a propitious lead candidate for the development of therapeutics, including anticancer drugs. This present mini-review highlights cyclopeptides from microbial-derived natural products that have demonstrated significant cytotoxicity or anticancer activities. Moreover, this mini-review also provides a look into the mode of action of anticancer cyclopeptides. Selected examples are given for the potent anticancer cyclopeptides isolated in the recent decade from fungi and bacteria from both terrestrial and marine origins. Naturally occurring cyclopeptides with canonical and non-canonical amino acids isolated from fungi, myxobacteria, actinomycetes, marine cyanobacteria, and microbes associated with marine organisms and their anticancer activity are featured herein.